Comparison of interrupted- and continuous-suture urethroplasty in tubularised incised-plate hypospadias repair: A prospective study - Archika Gupta (Taylor & Francis Group, 2017)
Objective: To compare the effect of interrupted- and continuous-suture urethroplasty on complication rates in Snodgrass tubularised incised-plate (TIP) hypospadias repair. Patients and methods: This was a prospective randomised study comprising 100 boys (age range 1â5â¯years) with primary subcoronal, distal- and mid-penile hypospadias who underwent repair from October 2010 to March 2015 in a tertiary care hospital. Boys with glanular, recurrent, and proximal hypospadias were excluded from the study. The boys were prospectively randomised into two groups: Group A, comprised 50 boys who underwent interrupted subcuticular suture Snodgrass TIP urethroplasty; and Group B, comprised 50 boys who underwent continuous subcuticular suture Snodgrass TIP urethroplasty. Outcomes were assessed in terms of complication rates and aesthetic appearance during follow-up. Results: There was no significant difference in the occurrence of complications between the groups. There were 21 complications, with 10 occurring in Group A and 11 in Group-B. Urethrocutaneous fistula was the most common complication in both groups (six in Group A and seven in Group B), the fistulae were <2â¯mm in nine patients and 3â5â¯mm in the remaining four. Partial glans dehiscence occurred in one patient in each group. One patient from each group also had superficial wound infection, meatal stenosis and urethral stricture respectively, all of which were managed conservatively. The resultant urinary stream was single and good in all patients of both groups. Conclusions: The type of suture technique had no significant effect on complication rates after Snodgrass hypospadias repair and thus the choice of technique depends on surgeon preference. Keywords: Hypospadias, Snodgrass TIP repair, Urethrocutaneous fistula, Urethroplasty